The Effectiveness of Sand Play Therapy on Social Skills and Adaptation of Children with Separation Anxiety - Ehsan Kazemi; Meisam Ashrafi; Maryam Sadat Hosseinzadeh Maryam Sadat Hosseinzadeh; Zahra Andalibipour; Shohreh Rajab Ali; Mehran Mohebian Far Mehran Mohebian Far (Iranian Journal of Educational Research)
Objective: The aim of this current research was to examine the effectiveness of sand play therapy in improving the social skills and adjustment of children experiencing separation anxiety. Methods: The research methodology utilized in this investigation was semi-experimental, employing a pre-test, post-test design with a control group. The specific population targeted for this study encompassed all children aged between 7 and 12 who had been diagnosed with separation anxiety disorder and were receiving counseling at the educational and training facility centers in Tehran in 2022. A sample of 30 individuals was chosen through convenience sampling and then randomly split into two groups of 15 participants each, designated as the experimental group and the control group. The research tools employed in this study consisted of the social skills questionnaires created by Karamati (2012) and the adaptability questionnaire by Sinha and Singh (1997). The sand play therapy sessions, comprising 8 sessions lasting 60 minutes each, were conducted by the researcher for the experimental group, while the control group did not undergo any training or therapy. Results: The outcomes of this study indicated that sand play therapy had a beneficial effect on the social skills and social adjustment of children with separation anxiety, resulting in an enhancement of their overall social functioning and adaptation. Conclusions: In light of these findings, it is recommended that educational counselors and psychologists integrate sand play therapy as an intervention to boost the social skills and adaptability of children grappling with separation anxiety in educational environments.